2014
DOI: 10.4314/ejhs.v24i0.4s
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Mortality Trends in Ethiopia

Abstract: BackgroundAlthough the magnitude of perinatal mortality in Ethiopia was among the highest in Sub Saharan Africa, there was no systematic review done to assess the trend and causes of perinatal death. The objective of this review was to assess the trend of perinatal mortality rate (PMR) and the causes attributed to perinatal deaths.MethodsStudies included in this systematic review were sixteen hospital and community based perinatal mortality studies, which were conducted between 1974 and 2013 using data concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 19 publications
8
65
6
Order By: Relevance
“…Another analysis in the same period also demonstrated that obstructed labor with or without uterine rupture was the leading cause of perinatal mortality (27%) (9). …”
Section: Introductionmentioning
confidence: 90%
“…Another analysis in the same period also demonstrated that obstructed labor with or without uterine rupture was the leading cause of perinatal mortality (27%) (9). …”
Section: Introductionmentioning
confidence: 90%
“…The causes of PM are numerous and vary according to the health status of the mother and access to antenatal care. About 99% of PM occurs in low-and middle-income countries [12]. In areas where pregnant women have access to quality healthcare services, congenital malformations, preterm birth, and intrauterine growth restriction are the leading causes of PM.…”
Section: Introductionmentioning
confidence: 99%
“…A review of births in Ethiopia from 1974 to 2013 found perinatal mortality rates ranging from 66 to 124 per 1000 births at the community level, and from 37 to 52 per 1000 births at the hospital level . The 2011 Ethiopian Demographic and Health Survey (EDHS) reported that Ethiopia's and Tigray's perinatal mortality rates were 46 and 51 per 1000 live births, respectively .…”
Section: Introductionmentioning
confidence: 99%